ADULT LITERACY AND HEALTH PROMOTION BEHAVIOR (HPB): A STUDY OF RURAL ADULT POPULATIONS IN RIVER STATE, NIGERIA - Patience, Agi (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Preventing illness and maintaining a healthy lifestyle both require actions that are beneficial to one's health. Literacy has various potential benefits for one's health and well-being, and these benefits are manifest in health promotion behavior. The present study examines the association between adult literacy and health promotion behavior in rural adults. A convenience sample of two hundred and eleven adults residing in the rural communities of River State, Nigeria, participated in the study. The respondents comprising males and females aged 40 to 65, completed a self-report measure of the adult literacy questionnaire and the health promotion lifestyle profile II. The result demonstrated a statistically significant, positive correlation between adult literacy and health promotion behavior, r (209) = .36, p < .001, with adult literacy contributing 21.2% of the variation in health promotion behavior. The finding has implications for developing adult literacy in rural communities in River State, Nigeria.